Cultures transpyrénéennes Les parures du sud-ouest de la France et du nord-ouest de l'Espagne au Premier âge du Fer (VIIIe-Ve s. a.C.) - Constantin, Thibaud (DAN@, 2023)
By his ornements, an individual communicates his or her social status, economic standing or membership of a group, whether through his culture or beliefs. Ornaments play a strong cultural and symbolic role and constitute a particularly rich source of information for archaeology. This work, result of a thesis, entitled « Cultures transpyrénéennes : les parures du sud-ouest de la France et du nord-ouest de l'Espagne au Premier âge du Fer (VIIIe-Ve s. a.C.) » is based on an exhaustive body of work from both old and recent data. The numerous developed analyses make it possible to draw up a summary reflection with a historical focus on the wearers of regional ornaments and to understand the interactions between the populations settled on either side of the Pyrenees during the First Iron Age.